Assessing the real implications for CO2 as generation from renewables increases - Dhruv Suri; Jacques de Chalendar; Inês M. L. Azevedo (Nature Communications)
Abstract Wind and solar electricity generation account for 14% of total electricity generation in the United States and are expected to continue to grow in the next decade. While increased renewable penetration reduces system-wide emissions, the intermittent nature of these resources disrupts conventional thermal plant operations. Generation displacement exhibits a nonlinear relationship, as thermal units forced to operate at suboptimal levels experience efficiency penalties. Here we show that as renewable generation rises, thermal plants often operate sub-optimally, increasing emissions when forced to respond to variability. Using hourly emissions and generation data from California and Texas, we find that solar and wind energy significantly reduce expected emissions under normal operating conditions - by 92.6% in California and 91.1% in Texas. However, if renewables force plants to operate inefficiently, emissions from natural gas and coal plants could increase by 12% to 26%. These results highlight the complex interactions between renewable energy growth and thermal plant emissions, indicating that careful management of renewables integration is crucial to minimizing overall system-level CO2 emissions, especially in electricity grids with inflexible thermal capacity.